Olá, pocoyo: a constituição da atenção conjunta infantil com o desenho animado - Costa Filho, José Moacir Soares da (2011)
Nowadays we are exposed to a plethora of contemporary cartoons which create interaction with the audience. With that in mind, the aim of this research is to analyze the relationship between children and cartoons in order to grasp how the process of joint attention is established with the aid of the television structure of the cartoon, as well as to understand how this process of joint attention may be important to the consolidation of linguistic reference. Considering research regarding joint attention, it is a fact that this process is usually studied considering children during their language acquisition period. However, in this paper, when observing the constitution of joint attention, this process is taken as a remaining part of children s routine after they have already acquired language, since it may provide necessary elements for the consolidation of linguistic reference. Aiming at focusing on our objective, we selected the Spanish cartoon Pocoyo, addressed at preschoolers, and we collected, during fortnight filming, data of two dyads mother-children in preschool age watching the before mentioned cartoon. As theoretical support to this research, we use theories which refer both to joint attention (BRUNER, 1975, 1983; TOMASELLO, 1995, 2003, 2005, 2011) and linguistic reference (BLÜHDORN, 1999; DIESSEL, 2006), and the structure of contemporary cartoons (GUNTER & MCALEER, 1997; MACHADO, 2005; SANTOS FILHO, 2008). Analysis show that the structure of Pocoyo contributes to the constitution of joint attention in two different formats: real and virtual. Moreover, we realize that, even though children whose data were analyzed had already acquired language, the structure of joint attention may be seen as a strategy which continues to be part of the children s interactions and contributes to the consolidation of the processes of language acquisition, emphasizing linguistic reference. As a result of our analysis, we observe that the interactive structure of the cartoon provides the establishment of joint attention, a process that is constituted as a scenery to the consolidation of spatial reference.